Reconstruction of Green?s function for multiplicative Sturm-Liouville problem - Yilmaz, Emrah; Gulsen, Tuba; Goktas, Sertac (Univ Nis, Fac Sci Math, 2023)
We construct multiplicative Green's (or 'Green's) function for 'Sturm-Liouville ('SL) equation. The basic properties of 'Green's function are given. Then, 'SL equation is evaluated by using 'Green's function. Effectiveness of Green's function in 'case will thus be seen by some examples.
Keywords: Multiplicative calculus; Green?s function; multiplicative Sturm-Liouville equation; eigenfunction; Eeigenvalue; Wron-skian; Boundary value problem